A home for teasel - McAllister, Margi (London, England : Scholstic, 2013)
A beautifully touching animal story by the author of Fawn: perfect for all you fans of Michael Morpurgo or Gill Lewis. Meet Gwen: the one nobody notices. What with her wild big sister and poorly little brother, she s used to being forgotten about. She has always dreamed of having a pony, but money isn t exactly raining from the sky. So Gwen does odd jobs, adding pennies to her pony fund. Until she meets Mrs Tilney. The old lady has a pony that needs looking after. Lending a hand is Gwen s dream come true. A natural with horses, she quickly bonds with Teasel. But then disaster strikes